Chemosensory stimulation during sleep: arousal responses to gustatory stimulation - Stuck, Boris; Moutsis, Tracy Thecla; Bingel, Ulrike; Sommer, Ulrich (Neuroscience, 2016)
The processing of nociceptive, visual, vibrotactile, thermal and acoustic stimuli during sleep has been extensively investigated in the past. Recently, interest has focused on the impact of olfactory stimulation on sleep. In contrast to all other sensory systems, olfactory stimulation does not lead to an increased arousal frequency, regardless of hedonicity and concentration. The impact of the second chemosensory system, gustation, on sleep however has not been investigated to date. Twenty-one normosmic and normogeusic volunteers of both genders, aged 19-33years, participated in the trial. Stimulation was performed with a gustometer using the following aqueous solutions: saccharose 20% (sweet), sodium chloride (NaCl) 7.5% (salty), citrate 5% (sour), and quinine 0.02% (bitter). A tasteless solution was used as negative control. Capsaicin, a strong trigeminal stimulus, served as positive control. Primary outcome was arousal frequency per stimulus in each sleep stage, as assessed with polysomnography. The frequency of arousals decreased in deeper sleep stages (N1: 211 arousals of 333 stimuli=63%, N2: 676/2728=25%, N3: 43/1378=3%, REM: 57/1010=6%). Statistically significant differences in terms of arousal frequency were found in N2 between the negative control and NaCl 100μl (p<0.001), saccharose 100μl, citrate 50μl & 100μl, and quinine 100μl (p<0.05). Capsaicin led to complete awakenings in 94% of stimuli (30/32). These results demonstrate that gustatory stimulation during sleep induces arousals depending on stimulus intensity and sleep stage, which is different to olfactory stimulation and may be related to differences in central processing of the two chemosensory systems.